DEVELOPMENT OF PHARMACY NETWORK IN SOVIET TAJIKISTAN IN THE FIRST HALF OF THE 20TH CENTURY - S.D. YUSUFI; A.R. NURZODA (Паёми Сино, 2025)
The organization and implementation of activities within a pharmacy network are crucial for a country's healthcare system, as they ensure that both the population and medical institutions have accessto essential medications. This article examinesthe development and organization of the pharmacy service during the Soviet era in the Republic of Tajikistan.